2008
DOI: 10.1186/1745-0179-4-15
|View full text |Cite
|
Sign up to set email alerts
|

Psychological problems in gastroenterology outpatients: A South Australian experience. Psychological co-morbidity in IBD, IBS and hepatitis C

Abstract: BackgroundIn independent studies, IBD, IBS and HCV have each been associated with a substantially increased risk of psychological problems such as depression and anxiety and impairment of quality of life compared to the general healthy population. However, the relative psychological burden for each of these diagnoses is unknown as it has never been compared contemporaneously at one institution. Current local data are therefore needed to enable an evidence-based allocation of limited clinical psychological reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
41
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 32 publications
5
41
1
Order By: Relevance
“…[3132] In the same studies IBS respondents were significantly older than those with HCV (Mean age 54 vs. 45) which is in accordance with our findings; although in our study this age effect is not statistically significant. The high proportion of economically inactive IBS respondents in our study is in accordance with previous studies which have reported that people with IBS are more likely to be unable to work.…”
Section: Discussionsupporting
confidence: 92%
“…[3132] In the same studies IBS respondents were significantly older than those with HCV (Mean age 54 vs. 45) which is in accordance with our findings; although in our study this age effect is not statistically significant. The high proportion of economically inactive IBS respondents in our study is in accordance with previous studies which have reported that people with IBS are more likely to be unable to work.…”
Section: Discussionsupporting
confidence: 92%
“…Sykes et al (2003) observed that anxiety tends to precede IBS onset and plays an important role in the development of IBS. In a South Australian study, Mikocka-Walus et al (2008) found that depression and anxiety were common in subjects with IBS symptoms. An excessive tendency to somatization was reported in population-based studies and in clinical studies (Locke et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Scores between 8–10 are indicative of a potential mental disorder 15. Data of the validated German version HADS‐D16 of the general German population14 as well as from large international medically ill populations17 and data of IBD patients18–27 are available. Its sensitivity and specificity as a screening method for mental disorder according to the criteria of the Diagnostic and Statistical Manual for Psychiatric Diseases (DSM‐III‐R) was 76% and 79%, respectively, with cutoff scores >8 in either HADS‐subscale in IBD patients 18…”
Section: Methodsmentioning
confidence: 99%